Perfil de suscetibilidade de isolados de Malassezia pachydermatis, comensais e patógenos, frente a agentes antifúngicos - Weiler, Caroline Borges (2012)
Malassezia pachydermatis is opportunistic yeast that primarily affects animals, being associated with dermatomycoses and ear diseases in dogs and cats. This is important yeast in veterinary medicine and therefore the knowledge of its susceptibility profile against various antifungal agents, is necessary to obtain success in treating and preventing relapses of infection. The aim of this study was to compare the susceptibility between pathogenic and commensal M. pachydermatis strains against ketoconazole, miconazole, clotrimazole, itraconazole, fluconazole, voriconazole, amphotericin B and nystatin. All isolates were tested by the broth microdilution method using the CLSI M27-A3 (2008). The strains isolated from infectious processes (G1) showed higher MICs than commensals strains (G2). The azoles ketoconazole, itraconazole and voriconazole showed excellent effectiveness against M. pachydermatis isolates. Differences in susceptibility to amphotericin B, nystatin, miconazole, clotrimazole and fluconazole were observed between G1 and G2 groups. It can be explained by the variation in the lipid content of the capsule surrounding the organism and the concentration of intracellular antioxidant enzymes. M. pachydermatis is important yeast in veterinary medicine and therefore the knowledge of its susceptibility profile against various antifungal agents, is necessary to obtain success in treating and preventing relapses of infection.